Measurements of heat transfer on hemispheres at rarefied flow conditions using liquid crystals - Donaldson, N; Doherty, L; Merrifield, J; Ireland, P (European Space Agency, 2021)
In the study of space debris re-entry heating, there are to this day significant uncertainties in the distribution of thermal fluxes incident upon re-entering spacecraft and debris. In order to improve the accuracy of such calculations, experiments have been conducted in the recently refurbished Oxford Low Density Tunnel (LDT) to characterise the heat transfer distribution over a pair of hemisphere-capped cylinders measuring 10mm and 15mm in diameter. These models were constructed of Perspex, and were designed as simple geometric analogues of satellite components such as those utilised by current debris simulation codes.